Innovation and sustainability in Human Resources Management: contributions from intrapreneurship /Inovação e sustentabilidade na gestão de recursos humanos: contributos do intraempreendedorismo - Neves, J. (Journal of Business and Legal Sciences / Revista De Ciências Empresariais E Jurídicas, 2024)
The hyper-dynamism of the external and internal environment of organisations, which the recent Covid pandemic has highlighted and which digitalisation is amplifying, seems to call into question the value placed on people, in the sense that they are constantly confronted with changes to the content of their work, with regulation of it, and in some cases even with the extinction of their jobs. Overcoming this situation requires human resource management (HRM) to have the capacity and imagination to identify new opportunities that refocus people in the context of the organisation and transform their management into a process that balances individual and organisational interests. Moreover, there is a consensus that people are the organisation's main transforming agent and the one who creates value. What can be done to boost this consensus? Fostering innovation and creativity, encouraging IE and organising people management on the basis of the quality model (plan, do, check and act) seems to be an appropriate way to keep the organisation competitive and sustainable. In order to meet the challenges of competitiveness and sustainability, organisations are constantly challenged to focus on adaptation, innovation and change. In this movement, the dynamics associated with the external and internal environments generate complex and sometimes paradoxical situations that condition the work of managers.